Perancangan Pencatu Daya Alat Electrostatic Precipitator dengan Solar Cell pada Cerobong Pengasapan Ikan - Prasojo, Agus; Haq, Lutfan Zainul; Prasetyowati, Sri Arrtini Dwi; Nugroho, Agus Adhi (Elektrika, 2023)
In Kendal, smoked fish producers generally use the hot smoking method, in which the fish is placed close to the smoke source and smoked for three to four hours. The upside is that it has a significant impact on supporting many human endeavors, such as in industrial fishing and food processing. While the negative impact on the environment, such as environmental damage due to global warming, and air pollution. To overcome this problem, a prototype of an environmentally friendly Electrostatic Precipitator chimney has been created. This prototype is operated using power from a Solar Power Plant (PLTS). The results of this study indicate the potential absorption of solar radiation by solar cells shows good efficiency in the first test, the efficiency of solar cells recorded the lowest value of 8.50%, the highest reached 15.76%, with an average of 13.03%. Furthermore, in the second test, the efficiency of the Solar Cell showed an increase, recording the lowest value of 12.83%, the highest reaching 17.19%, and an average of 14.72%. The best test is in the second test because the first test is cloudy and drizzling. By utilizing the intensity of solar radiation as a resource, the Electrostatic Precipitator can be operated quite well. In the two tests carried out, the average output power of solar panels reached 28.51 and 49.49 Watts. Meanwhile, for the power used as the input of the tool in the two experiments, the values recorded were 30.70 and 10.33 Watts. Keywords: Fumigation, Electrostatic Precipitator, PLTS (Solar Power Plant) ABSTRAK  Di Kendal, para produsen ikan asap umumnya menggunakan metode pengasapan panas, di mana ikan diletakkan dekat dengan sumber asap dan diasapi selama tiga hingga empat jam. Dampak positifnya adalah memiliki dampak yang signifikan untuk mendukung banyak usaha manusia, seperti di bidang indutsri perikanan dan pengolahan makanan. Sedangkan, dampak negatifnya terhadap lingkungan, seperti kerusakan lingkungan akibat pemanasan global, dan polusi udara. Untuk menangani masalah tersebut, telah dibuat sebuah prototipe cerobong Electrostatic Precipitator yang ramah lingkungan. Prototipe ini dioperasikan menggunakan tenaga dari Pembangkit Listrik Tenaga Surya (PLTS). Hasil penelitian ini menunjukkan potensi tingkat penyerapan radiasi matahari oleh Solar Cell menunjukkan efisiensi yang baik pada pengujian pertama, efisiensi Solar Cell tercatat nilai terendah sebesar 8,50 %, tertinggi mencapai 15,76 %, dengan rata-rata 13,03%. Selanjutnya, pada pengujian kedua, efisiensi Solar Cell menunjukkan peningkatan, mencatat nilai terendah sebesar 12,83 %, tertinggi mencapai 17,19 %, dan rata-rata sebesar 14,72 %. Pengujian terbaik terdapat pada pengujian kedua dikarenakan pengujian pertama terdapat cuaca mendung dan gerimis. Dengan memanfaatkan intensitas radiasi matahari sebagai sumber daya, alat Electrostatic Precipitator dapat dioperasikan dengan cukup baik. Pada dua pengujian yang dilakukan, rata-rata daya Output  panel surya mencapai 28,51 dan 49,49 Watt. Sementara itu, untuk daya yang digunakan sebagai Input alat tersebut dalam dua percobaan, nilai yang tercatat adalah 30,70 dan 10,33 Watt.